IMPLEMENTATION OF THE HEALTH BELIEF MODEL (HBM) CONCEPT ON THE USE OF THE COVID_19 VACCINE. POPULATION CROSS SECTIONAL STUDY IN WEST JAVA PROVINCE - Salman Salman; Muhammad Arief Setiawan; Astri Nurdiana; Nilasari Nilasari (Green Publisher, 2023)
The implementation of the concept of the health belief model (HBM) during this pandemic is an effective step in analyzing the reasons for individuals/society to want or not to carry out healthy behavior, especially in the use of covid_19 vaccination. This study aims to analyze the community's compliance in participating in the Covid_19 vaccination program based on a health belief model (HBM) concept approach which consists of perceived susceptibility, perceived seriousness, perceived benefits, and perceived seriousness. perceived barrier, perceived self-efficacy, self-efficacy during the Covid_19 pandemic. This type of quantitative research with a cross-sectional study design was carried out in West Java Province, sampling using accidental sampling technique. The research data was processed quantitatively by using multiple linear regression analysis method to measure the effect of the 6 components of HBM, namely (1) perceived susceptibility. (2). perceived seriousness, (3). perceived benefits, (4). perceived barrier, (5). perceived self-efficacy (6). self efficacy towards community compliance in participating in the Covid_19 vaccination program Perceived vulnerability, perceived seriousness, perceived barriers, perceived benefits, self-efficacy, cues to action, gender, and education had a significant relationship with community compliance in participating in the Covid-19 vaccine program with a p-value of 0.000. The most dominant factor in influencing people's adherence to the Covid-19 vaccine is self-efficacy with Exp (B) of 4,616. In this study, it was concluded that the dominant variable affecting community compliance in participating in the covid-19 vaccination program was the self-efficacy variable. Self-confidence that having the ability to obey and want to be vaccinated against covid-19, has the most effect on compliance in participating in the covid-19 vaccination program. People with good self-efficacy have a 4.2 times chance of being obedient to the covid-19 vaccine